Wireless communications and networks : 3g and beyond - Saha Misra, Iti (McGraw Hill Education (I) Pvt. Ltd, 2013)
Wireless communications and networks : 3g and beyond / Saha Misra, Iti. -- New Delhi: McGraw Hill Education (I) Pvt. Ltd., 2013 621.384 Sa131e2 2nd ed No. of Copies : 1